The Negative Effects of KPN00353 on Glycerol Kinase and Microaerobic 1,3-Propanediol Production in Klebsiella pneumoniae - Jeng, Wen-Yih; Panjaitan, Novaria S. D.; Horng, Yu-Tze; Chung, Wen-Ting; Chien, Chih-Ching; Soo, Po-Chi (Frontiers in Microbiology, 2017)
1,3-Propanediol (1,3-PD) is a valuable chemical intermediate in the synthesis of polyesters, polyethers, and polyurethanes, which have applications in various products such as cloth, bottles, films, tarpaulins, canoes, foam seals, high-resilience foam seating, and surface coatings. Klebsiella pneumoniae can produce 1,3-PD from glycerol. In this study, KPN00353, an EIIA homologue in the phosphoenolpyruvate (PEP):carbohydrate phosphotransferase system (PTS), was found to play a negative regulatory role in 1,3-PD production under microaerobic conditions via binding to glycerol kinase (GlpK). The primary sequence of KPN00353 is similar to those of the fructose-mannitol EIIA (EIIFru and EIIAMtl) family. The interaction between KPN00353 and GlpK resulted in inhibition of the synthesis of glycerol-3-phosphate (G3P) and correlated with reductions in glycerol uptake and the production of 1,3-PD. Based on structure modeling, we conclude that residue H65 of KPN00353 plays an important role in the interaction with GlpK. We mutated this histidine residue to aspartate, glutamate, arginine and glutamine to assess the effects of each KPN00353 variant on the interaction with GlpK, on the synthesis of G3P and on the production of 1,3-PD. Our results illuminate the role of KPN00353 in 1,3-PD production by K. pneumoniae under microaerobic conditions.